2020
DOI: 10.1021/acs.jpcc.9b12045
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline Cellulose Confined in Amorphous Carbon Fibers as Capacitor Material for Efficient Energy Storage

Abstract: The development of sustainable and renewable energy storage systems is a promising approach toward steady and reliable energy supply. In this study, cellulosic palm loofah fibers were used as a precursor to produce amorphous carbon (Am-C) with retained crystalline cellulosic planes via a simple activation method. The Am-C exhibits a fairly high BET surface area of 2000 m2/g and a 3D-microporous structure with small mesopores. The symmetric Am-C//Am-C supercapacitor device tested in 1.0 M NaCl aqueous electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…have been used as the supercapacitor electrode material. Carbon materials can provide high surface area for the EDL and high stability to the Faradic materials in the electrode assembly . One of the interesting carbon sets is the Fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…have been used as the supercapacitor electrode material. Carbon materials can provide high surface area for the EDL and high stability to the Faradic materials in the electrode assembly . One of the interesting carbon sets is the Fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the C-Flax sample had a high micropore ratio with the V mi /V total = 75%, which makes it highly competitive with other porous carbon derived from natural products such as hemp [ 39 ], animal bones [ 40 ], and argan seed shells [ 21 ]. The high SSA together with the microporous structure of C-Flax provides extra space for electrolyte ions, which is crucial for EDLC systems [ 41 , 42 , 43 ] and therefore predispose C-Flax for supercapacitor applications.…”
Section: Resultsmentioning
confidence: 99%
“…A maximum specific energy of 43.11 Wh kg À1 was obtained, whereas the power density reached to a maximum value of 20 kW kg À1 , which are well comparable to the best performing supercapacitors available in the literature as compared in Figure 4f and Table 1 as well. [33][34][35][36][37][38][39][40][41][42][43] The superior electrochemical energy storage performance by ATA 700 char as compared with other chars can be attributed to the combined physical as well as chemical characteristics. The hierarchical porous architecture with distributed pore width has played crucial role in addition to the moderate pore volume and specific surface area, and balanced chemical contents, such as considerable sp 2 -C proportion and moderate amount of heteroatoms-especially the higher graphitic/N─C and C─P bonding networks.…”
Section: Resultsmentioning
confidence: 99%
“…[2,4] A clear conclusion on the best heteroatom(s), the atomic configuration of the dopant(s), and/or the defect-type in a graphitic carbon lattice for energy storage has not yet been achieved, because the related parameters are exclusively interdependent.In a complete contrast, very recently, the amorphous carbon-based materials have been reported to demonstrate attractive energy storage and conversion applications, such as in electrochemical batteries with high storage capacity and long-term stability, primarily owing to their disordered and defect-rich structures. [6][7][8][9][10][11][12][13][14][15] As such, it has been reported that the N-doped amorphous carbon sphere is more active for oxygen reduction reaction in 0.5 M H 2 SO 4 medium than their graphitic counterparts due to the fact that the micropores in amorphous carbon phase close down during graphitization process along with the decrease in N content. [14] Honda et al reported that the disordered sp 2 clusters in amorphous carbon or a mixed carbon state (sp 2 þ sp 3 C matrix) are more beneficial to electrocatalytic activities than pure graphitic carbons due to abundance in trapped charged centers.…”
mentioning
confidence: 99%
See 1 more Smart Citation